Prenatal exposure to air pollution and maternal stress predict infant individual differences in reactivity and regulation and socioemotional development. (17th February 2022) - Liu, Ran; DeSerisy, Mariah; Fox, Nathan A.; Herbstman, Julie B.; Rauh, Virginia A.; Beebe, Beatrice; Margolis, Amy E.
Abstract : Background: Humans are ubiquitously exposed to air pollutants including polycyclic aromatic hydrocarbons (PAH). Although most studies of prenatal exposures have focused on psychopathology in childhood or adolescence, the effects of air pollutants on early emerging individual differences in reactivity and regulation are of growing concern. Our study is the first to report effects of prenatal exposure to PAH and maternal stress on infant reactivity and regulation. Methods: Participants included 153 infants (74 girls and 79 boys). Prenatal exposure to PAH was measured via personal air monitoring during the third trimester of pregnancy. Maternal perceived stress was measured via self‐report. We assessed infant orienting/regulation (OR), surgency (SE), and negative affectivity (NA) at 4 months using the Infant Behavior Questionnaire. We measured infant socioemotional outcomes at 12 months using the Brief Infant‐Toddler Social & Emotional Assessment Questionnaire. Results: Infants with higher prenatal PAH exposure and of mothers with higher stress had lower OR at 4 months, which predicted lower competence at 12 months. Infants with higher prenatal PAH exposure had lower SE at 4 months, which predicted more behavioral problems at 12 months. Prenatal exposure to PAH had no effects on infant NA at 4 months, although NA was associated with greater behavioral problems at 12 months. Conclusions: Infant reactivity and regulation, as early makers of child psychopathology, can facilitate timely and targeted screening and possibly prevention of disorders caused, in part, by environmental pollution. A multifaceted approach to improve environmental quality and reduce psychosocial stress is necessary to improve the developmental outcomes of children and most specially children from disadvantaged communities that disproportionately experience these environmental exposures.